SINTESIS SENYAWA orto-FENILAZO-2-NAFTOL SEBAGAI INDIKATOR DALAM TITRASI - Suirta, I W. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010, 2012)
Synthesis of o-fenilazo-2-naphtol used as indicator in titration has been conducted in this research. The synthesis was carried out by coupling of diazonium chloride salt with 2-naphtol, and aniline. The product was characterized using spectroscopy techniques (IR, 1HNMR, and MS), while the pKHIn was determined using UV-vis spectrometer. The application of the product as indicator in titration was compared to methyl-orange. The synthesis gave a red crystal with 62.51 % yield. Infra red spectra analysis showed the presence of characteristic functional groups such as–OH, CH-aromatic, C=C, N=N, CN, CO, and a peak indicated substituents at ortho position. 1HNMR showed three separated peaks. Mass spectra gave molecular ion peak (M+) at m/z 248. The red crystal obtained melted at 128-131oC. Based on spectroscopy analysis and melting point, it can be concluded that the product was o-fenilazo-2-naphtol. The product had a pKHin of 3.16, therefore it can be used as indicator for acid-base titration which showed equivalent point at pH 5.
Keywords: syntesis, indicator, spectroscophy